5 - Economic Decolonisation and the Role of the Central Bank in Postcolonial Development in Tunisia - Ben Rouine, Chafik (Africa Development, 2022)
Overserving how the hegemonic neoliberal model of central banking works to undermine African agency and development in the present day, this article charts an alternative path, drawing from Tunisia’s efforts to decolonise their monetary institutions in the immediate post-independence period. Tunisia’s construction of a developmentalist Central Bank played a critical role in mobilising resources to facilitate their post-independence agrarian reform agenda and industrialisation plans. Key characteristics of this model included working in tandem with the government towards shared objectives, mobilising domestic resources to finance development plans, and intervening directly through methods like incentivised savings and subsidised loans for strategic sectors. This is in contrast with the neoliberal model in which central banks are independent from the government, focused on controlling inflation above all else, and exclusively use indirect methods like interest rates to conduct monetary policy. The article highlights the progressive and feminist potential of central bank reform in the contemporary period as a key mechanism for Africa’s economic transformation.